Drinking Water Sodium and Elevated Blood Pressure of Healthy Pregnant Women in Salinity-Affected Coastal Areas - Scheelbeek,PF; Khan,AE; Mojumder,S; Elliott,P; Vineis,P (Hypertension, 2016)
Coastal areas in Southeast Asia are experiencing high sodium concentrations in drinking water sources that are commonly consumed by local populations. Salinity problems caused by episodic cyclones and subsequent seawater inundations are likely (partly) related to climate change and further exacerbated by changes in upstream river flow and local land-use activities. Dietary (food) sodium plays an important role in the global burden of hypertensive disease. It remains unknown, however, if sodium in drinking water-rather than food-has similar effects on blood pressure and disease risk. In this study, we examined the effect of drinking water sodium on blood pressure of pregnant women: increases in blood pressure in this group could severely affect maternal and fetal health. Data on blood pressure, drinking water source, and personal, lifestyle, and environmental confounders was obtained from 701 normotensive pregnant women residing in coastal Bangladesh. Generalized linear mixed regression models were used to investigate association of systolic and diastolic blood pressure of these-otherwise healthy-women with their water source. After adjustment for confounders, drinkers of tube well and pond water (high saline sources) were found to have significantly higher average systolic (+4.85 and +3.62 mm Hg) and diastolic (+2.30 and +1.72 mm Hg) blood pressures than rainwater drinkers. Drinking water salinity problems are expected to exacerbate in the future, putting millions of coastal people-including pregnant women-at increased risk of hypertension and associated diseases. There is an urgent need to further explore the health risks associated to this understudied environmental health problem and feasibility of possible adaptation strategies.